(Un)earthly governance: beyond functional frameworks to flourishing spacescapes. Issue 2 (3rd August 2021) - Mouat, Clare M.; Techera, Erika Jane Edith; Notebaert, Lies; Blake, Meredith; Barker, Renae
Abstract : Purpose: Humanity has a weakness in how we approach the "challenge" of using outer space. This paper aims to show how the global and national frameworks that address our planetary activities and crises are inadequate for the opportunities and challenges of life in outer space. Design/methodology/approach: The authors draw on multidisciplinary perspectives to refine an organising governance framework that better showcases the challenges and pathways needed for living and thriving in space-age. The authors prioritise two key pillars and overview the practical and social implications that space-age humanity must address. Findings: Social sciences and humanities are vital to problematising post-war colonial legacies of governance by distinguishing the unique and overlooked challenges for thriving and working offworld and identifying progressive research agendas. Research limitations/implications: The highlighted agenda has implications for collaborative research institutes and project design. As the vital basis for continuous learning, university-based research institutes span bodies of knowledge, experience, convention and imagination that can support vibrant and overdue debate on good governance that is out of this world. Practical implications: This expansive approach has practical implications for the decision-making processes and subjects of spacescape, from reconciling the space commons with prospecting and human occupation to potential governance regimes that capitalise on the zeal for moving beyond merely "existing" off-world. Social implications: Examining the governance deficit as we pursue developing spacescape frontiers is an enriching (not reductionist) agenda that deliberately troubles the existing and emerging regime for governing our scientific and imagined off-world society. Originality/value: This framework appeals to humanity's highest evolution in co-producing a fair and flourishing off-world governance framework (beyond replicating planetary regimes).